Hematuria following Kidney Tumorectomy: Can it Hide an Arteriovenous Fistula?. Issue 3 (July 2015) - Pavan, Nicola; Liguori, Giovanni; Vedovo, Francesca; Bucci, Stefano; Bertolotto, Michele; Trombetta, Carlo
We present the case and radiologic images of a 64-year-old man who presented with gross hematuria and fever 2 months after undergoing retroperitoneal partial nephrectomy for a 4.7 × 4.6 cm papillary renal cell carcinoma. Angio-TC demonstrated an aneurysmatic dilatation of the anterior inferior segmental artery of the right kidney with an art-riovenous fistula; the patient was treated with angiography and selective cannulation by deploying 4 platinum coils. At follow-up, we used contrast-enhanced ultrasound to monitor coil embolization of the renal artery pseudoaneurysm.